(untitled) (Journal of Geography and Environmental Management, 2024)
The work is devoted to the assessment of the annual resources of the Aral-Syrdarya water basin’s river flow. Annual river runoff resources were estimated on the basis of observed and conditionally natural runoff, while the values of local runoff and inflow coming from neighboring countries were separated. The assessment of the resources of the local runoff of the studied territory was carried out by the method of equidistant values. For this purpose, work was carried out on the reconstruction of the observation series of reference points and, based on the selected calculation period for 1932-2019, the statistical characteristics of the annual runoff were determined (the average long-term value of the runoff volume, coefficients of variation and asymmetry). According to the results of the assessment, the total resources of the river flow of the Aral-Syrdarya water basin for the long–term period from 1932 to 2019 on average amount to 21,5 km3, of which: resources formed within Kazakhstan – 3,22 km3, resources coming from outside - 182 km3. During the disturbed period, local runoff, relative to the conditionally natural period, decreased by 4,66%, inflow from outside decreased by 4,98%, and total water resources by 4,92%.